2019
DOI: 10.3390/diagnostics9040206
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenic Factors May Have No Impact on Outcomes in Ovarian Cancer Patients

Abstract: Although the prognostic value of sarcopenic factors, such as loss of muscle mass and quality, have been widely reported in patients with cancer during the last decade, the value in those with ovarian cancer remains unclear. Therefore, this study evaluated the prognostic impact of sarcopenic factors in patients with ovarian cancer. We retrospectively evaluated the data of 94 ovarian cancer patients who underwent surgery and chemotherapy at the Shimane University Hospital between March 2006 and 2013. Preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 36 publications
1
26
1
Order By: Relevance
“…Most studies were conducted in Western populations whose body composition is different from that of Asians. Recently, a Japanese retrospective study showed results similar to those of our study; pre-treatment SMI was not associated with ovarian cancer patients' PFS and OS [19]. However, that study included early-stage disease and histologic types other than HGSOC, which is definitely different compared to our study.…”
Section: Discussioncontrasting
confidence: 54%
“…Most studies were conducted in Western populations whose body composition is different from that of Asians. Recently, a Japanese retrospective study showed results similar to those of our study; pre-treatment SMI was not associated with ovarian cancer patients' PFS and OS [19]. However, that study included early-stage disease and histologic types other than HGSOC, which is definitely different compared to our study.…”
Section: Discussioncontrasting
confidence: 54%
“…The flow diagram is illustrated in Figure 1. Fifteen studies6–12 20–27 were included in this systematic review, of which six studies were included in the meta-analysis 6–12. (Online supplementary Table S2 lists all excluded studies9 18 28–33 and the reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 7420 to 323 patients 12. Three studies were performed in Germany,7 12 27 three in The Netherlands,9–11 five in the USA,12 20 23 25 26 three in Japan,21 22 24 and one in Austria 10. Fourteen studies were retrospective and one was prospective 20.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations